Rancang Bangun Pemantau dan Pengendali Lampu Bersumber Panel Surya Menggunakan Arduino Berbasis Web - Dinari Gustiana (Politeknik Negeri Malang, 2018)
In the Modern Era, a source of electrical energy is very necessary, given the large number of electronic equipment that really requires a source of electrical energy. Solarcell is a device or component that can convert light energy into electrical energy. However, the energy used in this solar panel needs to be considered the efficiency of its use. Therefore it is necessary to monitor currents and voltages and loads in real time to determine the energy needs of solar panels for lamps. Monitoring of voltage, load and current on this solar panel is based on a microcontroller. The voltage generated by the solar panel and the battery voltage is measured using a sensor. It takes a Web and a modem device to send solar panel measurement data from a distance, with remote monitoring makes it easier to find out what the voltage and load is without having to be in place of the solar panel. Web as a control for lights, blackouts, dim and bright lights, on the web can monitor voltage and current values. The results of the microcontroller ADC are able to send data to the web. The data stored in the ms.excel file contains the voltage from the solar cell, the current at the load and the time when storing and charging the battery. The lights can only last 5 hours when all loads are active (ON), while charging (charging) for 13 hours when the battery is empty.